ANALISIS JALUR DISTRIBUSI SAYURAN BUNGA KOL (Brassica oleraceae) DARI PETANI DI KECAMATAN BATURITI HINGGA KONSUMEN DI KOTA DENPASAR - Arifin, Nur; Suryawan Wiranatha, Anak Agung P.A.; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni)
The objective of the study were: 1 to know the type of distribution channel of cauliflower, 2) to determine the marketing and profit margins of each distribusion channel, 3) to determine the lowest and highest profit margin from the distribution channels of cauliflower at District of Baturiti to consumers in Denpasar. This study used survey method. The population in this research was the cauliflower growers in 3 Subak Baturiti. The samples used in this study were 25 farmers cauliflower. There were 5 distribut ion channels of cauliflower from Baturiti to Denpasar, there are 5 lines: Line 1) farmers - wholesalers -traditional market retailers - consumers; lane 2) farmers - wholesalers - retailers supermarket - consumers; 3) farmers - collectors - wholesalers - retailers – consumers, 4) farmers -collectors - consumer (hotel); and 5) farmers - the mediator - wholesaler - consumer (catering). Marketing margins and profit margins of each channel were as follows: 1) Rp 6.000 and 5.098; 2) Rp 14.000 and 10.797; 3) Rp 7.000 and 4.754; 4) Rp: 4.000 and 3.462; 5) Rp 8.250 and 4.385. The lowest marketing and profit margins was in channel 4, while the highest marketing and profit margin was in channel 2.
Keywords: 97,